2025 recycling target: Only 10 EU countries on track - Adriana Neligan (Institut der deutschen Wirtschaft (IW), 2018)
Two years after adopting the Circular Economy Package, EU institutions finally agreed on new EU waste rules. Despite lower recycling targets as originally envisaged, most countries still have to push recycling to meet the goals. A single method of determining recycling rates was also decided, but an exemption will continue to allow for disparate recycling rates.
Keywords: 330